Pilgrimage Site Beyond Politics: Experience of the Sacred and Inter-religious Dialog in Bosnia - Belaj, Marijana; Martić Zvonko (2014)
The chapter analyzes ecumenism and inter-religious 'bottom-up dialogue' in Olovo, a pilgrimage (Catholic) shrine shared by Muslims and Catholics. Although one may observe occasional conflicts in Olovo as well, throughout the history and nowadays this pilgrimage site has functioned as a space of inter-religious dialogue and ecumenism. The chapter deals with the dialogue of life (the way living space is shared) and the dialogue through actions (people’s solidarity in extraordinary and everyday conditions). The dialogue of religious experience is highlighted due to the fact that a shared experience of the sacred within the shrine is stressed both in historical testimonies and in the contemporary interaction between the two religions in Olovo. The same goes for the sharing of pilgrimage time and space, as well as the common set of narratives linked to the sacred and experiences of the sacred.
ENG